Mengembangkan Moderasi Beragama Mahasantri Melalui Ta’lim Ma’hadi di Pesantren Mahasiswa - Maskuri, Maskuri; Ma'arif, A. Samsul; Fanan, M. Athoiful (J-PAI: Jurnal Pendidikan Agama Islam, 2020)
The article describes and analyzes ta’lim ma’hadi in al-Hikam Malang Student Islamic Boarding School and the values implemented to develop the moderate character of the mahasantri religion. This study used a qualitative approach with a case study design. The data in this study were taken through interviews, observation, and document techniques. This study indicates that the al-Hikam Malang student boarding school uses three strategies in religious moderation, namely, nurturing patterns, teaching patterns, and religious patterns. The three strategies are integral in the curriculum that is implemented there. Through the applied curriculum, kyai and asatidz as qudwah hasanah internalize the values of justice, balance, harmony, moderation. As well as being a moderate Muslim, the mahasantri al-Hikam graduate is expected to become a successful entrepreneur.